Implementation of Satrescrim Face Recognition in Investigations to Enforce the Theft Law with Weights at the Sidoarjo Polresta - Handoko, Abiel Tegar Putra (Police Studies Review, 2024)
Robbery with aggravating circumstances is the crime with the highest crime index at Polresta Sidoarjo from 2020 to 2022. The handling process uses face recognition technology. Face recognition is a method of identification that focuses on facial features. This research aims to describe how face recognition works in assisting the investigation process of the Pidum Unit at Satreskim Polresta Sidoarjo in resolving cases of robbery with aggravating circumstances. The focus of this research is to analyze the factors that influence face recognition in helping to locate suspected perpetrators during the investigation conducted by the Inafis Unit of Satreskrim Polresta Sidoarjo. The concepts and theories used include the concept of implementation, the concept of face recognition, the concept of assistance from the Inafis unit in cases of robbery with aggravating circumstances, and the concept of investigation according to Article 1, Clause 5 of the Criminal Code (KUHP). The theories applied are the organizational resource theory, SWOT theory, and law enforcement theory. The research method employed is field research and case studies, using a qualitative approach and descriptive analytical research type. Data sources are obtained from primary and secondary data through interviews, observations, and literature studies. The scope of the research is the Satreskrim Polresta Sidoarjo from 2020 to 2022. The research results indicate that the use of face recognition by the Inafis unit in assisting the investigation of robbery with aggravating circumstances in the Pidum Unit of Polresta Sidoarjo will be effective if the data from Inafis is complete and up-to-date. The use of face recognition in the investigation unit for resolving robbery with aggravating circumstances at crime scenes that have blurry CCTV footage affects the effectiveness of the investigation. This situation impacts the data input into the application because the results from the CCTV footage taken by the Inafis unit require analysis, and the data obtained cannot be directly input into the Inafis tools available.